On the Large Synchronous Machine Parameters Calculatioin - Ioan Adrian Viorel; Jean Jacques Simond; Mai Tu Xuan; Liliana Vicol (Advances in Electrical and Electronic Engineering, 2004)
The large synchronous generators were intensively studied, but not so many papers are entirely dedicated to the analythical calculation of the generator´s parameters. Therefore any contribution should be welcomed if it offers an improvement in the existing procedures or formulae. The paper is dealing with the large synchronous generator smagnetizing and leakage inductances calculation. A coherent algorithm is presented and the calculated parameters for a generator are given.